2017
DOI: 10.5194/acp-2017-541-ac2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Response to Anonymous Referee #2 statistic significance

Anonymous

Abstract: The long-term temperature changes of the mesopause region at the hydroxyl molecule OH (6-2) nighttime height and its connection with the geomagnetic activity during the 23rd and beginning of the 24th solar cycles are presented. Measurements were conducted with an infrared digital spectrograph at the Maimaga station (63 • N, 129.5 • E). The hydroxyl rotational temperature (TOH) is assumed to be equal to the neutral atmosphere temperature at the altitude of ∼ 87 km. The average temperatures obtained for the peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
2
1
0
Order By: Relevance
“…Shirzad et al [16] reported that application of GA 3 60 ppm increased the number of fruits per plant and yield in bittergourd. These findings were similar with [17] in cucumber, Dalai et al, [18] in cucumber [19][20][21].…”
Section: Yield Parameterssupporting
confidence: 93%
“…Shirzad et al [16] reported that application of GA 3 60 ppm increased the number of fruits per plant and yield in bittergourd. These findings were similar with [17] in cucumber, Dalai et al, [18] in cucumber [19][20][21].…”
Section: Yield Parameterssupporting
confidence: 93%
“…Zn deficiency causes the ribosomes to break down, which affects protein metabolism [31]. These findings were in accordance with Krishna [32] and Zeng et al, [10] who also reported a significant positive effect of zinc treatment on crude protein content [33][34][35].…”
Section: Quality Of Seed Of Soybeansupporting
confidence: 79%
“…In Pakistan tomato yield is about 574.0 thousand tons. Area under cultivation is 58 thousand hectares while its yield is 98 thousand hectogram per hector (Anonymous, 2013).…”
Section: Introductionmentioning
confidence: 99%